A RANCANG BANGUN ALAT PAKAN DAN MINUM AYAM PETELUR BERBASIS ARDUINO : RANCANG BANGUN ALAT PAKAN DAN MINUM AYAM PETELUR BERBASIS ARDUINO - Andrias, Andrias Abi Widyanto; Asril; Dwi Winarti (Universitas Ngudi Waluyo, 2023)
Technological advancement in the context of layer chicken farming. In the modern world, technology has rapidly evolved and provided significant contributions across various aspects of human life, including the field of animal husbandry. The layer chicken farm of CV. PRASASTY in Sarimulya Village, Jujuhan Ilir, Bungo, Jambi, produces a substantial number of eggs daily. However, feeding the layer chickens poses a challenge to time and labor efficiency. In this study, the author focuses on the design of an Arduino-based device for feeding and watering layer chickens. The objective of this research is to address the challenges in feeding practices within layer chicken farming. The research process involves stages such as problem identification, literature review, component selection, design of hardware and software components, device programming, testing, and device implementation. The test results demonstrate the successful implementation of the Arduino-based feeding and watering device for layer chickens, which aids in streamlining the feeding and watering process. The device is integrated with the Blynk application and can automate the scheduling of feeding and watering. Consequently, this device contributes to labor efficiency within the poultry farming workforce and enhances egg production from layer chickens. The development of this Arduino-based feeding and watering device has proven to be effective in addressing feeding challenges within layer chicken farming, offering a positive impact on time and labor efficiency while augmenting egg production from layer chickens.